Assessment of radiation dose due to natural radionuclides in various cement samples. (1st January 2011) - Mehra, Rohit; Bala, Pankaj; Badhan, Komal; Sonkawade, R.G.
Samples of Ordinary Portland Cement (OPC) and Portland Pozzolana Cement (PPC) from five companies were analysed for the measurement of 226 Ra, 232 Th and 40 K using a HPGe detector based on high-resolution gamma spectrometry system. The measured activity in the selected OPC cement samples varies from 19.24 Bq kg −1 (JK Laxmi) to 40.73 Bq kg −1 (JayPee), 29.49 Bq kg −1 (JK Laxmi) to 42.17 Bq kg −1 (JayPee) and 228.25 Bq kg −1 (JK Cement) to 304.98 Bq kg −1 (Binani) for 226 Ra, 232 Th and 40 K, respectively. The concentration of radium, thorium and potassium in the selected PPC cement samples varies from 22.50 Bq kg −1 (JK Laxmi) to 48.83 Bq kg −1 (Binani), 30.74 Bq kg −1 (JK Laxmi) to 70.48 Bq kg −1 (Binani) and 267.94 Bq kg −1 (Binani) to 328.88 Bq kg −1 (JayPee), respectively. Radium equivalent, annual effective dose, absorbed dose and hazard indices were also calculated for the measured samples.